Perceived social support, perceived stress, and quality of sleep among COVID-19 patients in Iran: assessing measurement invariance of the multidimensional scale of perceived social support across gender and age - Habibi Asgarabad, Mojtaba; Vahabi, Zahra; Cheung, Ho Nam; Ahmadi, Reza; Akbarpour, Samaneh; Sadeghian, Mohammad Hossein; Etesam, Farnaz (Frontiers in Psychiatry, 2024)
Background: Perceived social support (PSS) plays a considerable role in mental health. The Multidimensional Scale of Perceived Social Support (MSPSS) is one of the most widely used scales, leading to much research evidence. The present study investigated its measurement model, equivalence across gender (male and female) and age groups (older patients= above 60 and non-older patients= below 60), and concurrent validity. Methods: A cross-sectional survey was conducted between March and October 2020, on patients hospitalized due to COVID-19 in Tehran, Iran. The scales were administered to 328 COVID-19 patients (54.6% male, aged 21 to 92) from two general hospitals; participants completed MSPSS (including friends, family, and significant others subscales), Pittsburgh Sleep Quality Index (PSQI, include sleep latency, subjective sleep quality, habitual sleep efficiency, sleep duration, use of sleep medication, daytime dysfunction, and sleep disturbances subscales), and the Perceived Stress Scale-10 (PSS-10, to assess patients' appraisal of stressful conditions). Results: The MSPSS three-factor structure was confirmed among COVID-19 patients by Confirmatory Factor Analysis (CFA). The results support the MSPSS internal consistency and configural, metric, and scalar invariance across gender and age groups. Nevertheless, small but significant differences were found across ages based on the latent factor mean of the MSPSS from friends, with a lower mean level in older patients. The coefficients of Cronbach's alpha (ranging from .92 to .96), the ordinal theta (ranging from .95 to .98), and Omega (ranging from .93 to .97) suggested high internal consistency of MSPSS. The concurrent validity of MSPSS was evidenced by its significant negative correlation with PSS-10 (τb = -.13, p < .01) and also subjective sleep quality (τb = -.22, p < .01), sleep disturbances (τb = -.26, p < .001), and daytime dysfunction (τb = -.26, p < .001). Conclusions: The MSPSS was valid and reliable for measuring individuals' perception of social support between males and females and older and non-older COVID-19 patients.